ETHNOLINGUISTIC SPECIFICITY OF OB-IRTYSH INTERFLUVE TOPONYMS (AS REVEALED BY HYDRONYMS OF KHANTY ORIGIN) - Y. V. Islamova; Ю. В. Исламова (Кемеровский государственный университет, 2016)
The paper provides an overview of the main factors behind the formation of distinctive toponymy of the Ob Ugric peoples. The paper examines the substrate names of water sources of Khanty origin in the aspect of authors’ linguistic identity. Conclusions are made about the causes of composite names. Extensive illustrative material is accompanied by semantic-etymological interpretation. В данной статье представлен обзор основных факторов, обусловивших формирование самобытной топонимии обских угров. В работе анализируются субстратные названия водных источников хантыйского происхождения в аспекте лингвоэтнической самобытности номинаторов. Делаются выводы о причинах возникновения многокомпонентых онимов. Иллюстрационный материал сопровождается семантико-этимологической интерпретацией.